2018
DOI: 10.1186/s13048-017-0376-6
|View full text |Cite
|
Sign up to set email alerts
|

A protocol to isolate and qualify purified human preantral follicles in cases of acute leukemia, for future clinical applications

Abstract: BackgroundAutotransplantation of cryopreserved ovarian cortex can be associated with a risk of cancer cell reseeding. This issue could be eliminated by grafting isolated preantral follicles. Collagenase NB6 is an enzyme produced under good manufacturing practices (GMP) in compliance with requirements for tissue engineering and transplantation in humans and thus can be used to isolate preantral follicles from ovarian tissue in the framework of further clinical applications. Multicolor flow cytometry is an effec… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
12
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
4
4
2

Relationship

1
9

Authors

Journals

citations
Cited by 20 publications
(13 citation statements)
references
References 75 publications
(85 reference statements)
1
12
0
Order By: Relevance
“…Follicles diameter in Group 1 has signi cantly smaller than Group 2 (44.5 ± 11.4 μm vs 45.8 ± 11.1 μm, p < 0.01). This were similar to the result obtained by Mouloungui et al who reported the similar mean diameter of follicles treatment by Liberase DH (45.2 ± 8.2 μm) [27].…”
Section: Yield Of Isolated Folliclessupporting
confidence: 92%
“…Follicles diameter in Group 1 has signi cantly smaller than Group 2 (44.5 ± 11.4 μm vs 45.8 ± 11.1 μm, p < 0.01). This were similar to the result obtained by Mouloungui et al who reported the similar mean diameter of follicles treatment by Liberase DH (45.2 ± 8.2 μm) [27].…”
Section: Yield Of Isolated Folliclessupporting
confidence: 92%
“…A major benefit of isolating follicles from the ovarian stroma is the potential to reduce any malignant cells that could be introduced during transplantation. Although we did not validate this with our isolation methods, there have been reports suggesting that follicle isolation can significantly decrease cancer cells prior to implantation 15,69 . In addition, our isolated ovarian cell suspensions were not filtered to contain follicles alone.…”
Section: Discussionmentioning
confidence: 70%
“…In view of this risk, various research teams worldwide have been investigating alternative approaches, including: (i) in vitro (ex vivo) culture of follicles [122][123][124], and (ii) in vivo (post-transplantation) growth of isolated preantral follicles inside a transplantable artificial ovary [92,[125][126][127][128][129][130][131][132][133][134][135][136][137][138][139][140]. The primary objective of an artificial ovary is to safely transplant ovarian follicles, while ensuring secretion of sex hormones and development of fertilizable mature oocytes.…”
Section: The Why and How Of The Artificial Ovarymentioning
confidence: 99%